Pengaruh Preferensi Merek, Brand Awareness, dan Variasi Produk terhadap Keputusan Pembelian Marugame Udon di Tunjungan Plaza Surabaya - Halawatul Ulum; Ni Made Ida Pratiwi; Ayun Maduwinarti (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the influence of Brand Preference (X1), Brand Awareness (X2), and Product Variety (X3) on Purchase Decision (Y) at Marugame Udon in Tunjungan Plaza Surabaya. As a Japanese fast-food restaurant, Marugame Udon faces intense competition in the culinary industry, making it essential to understand the factors that influence consumer behavior. This research employs a quantitative descriptive approach, with data collected through an online questionnaire distributed to 100 respondents who are customers of Marugame Udon. The results show that all three independent variables significantly affect purchase decisions, both partially and simultaneously. Brand preference is identified as the most dominant factor influencing consumers, followed by brand awareness, which enhances brand recognition, and product variety, which offers menu flexibility and increases consumer satisfaction. This study recommends that Marugame Udon's management continue to strengthen brand image, improve promotional efforts, and maintain product innovation to enhance customer loyalty and purchase decisions.